Sound absorption properties of industrial tea-leaf-fiber waste materials - (:unkn) unknown (My University, 2007)
Sound absorption constitutes one of the major requirements for human comfort today. Sound insulation requirements in automobiles, in manufacturing environments, and in equipments, generating higher sound pressure, strives the need to develop more efficient and economical ways of producing absorption materials. Traditionally, economics of the research has enforced the researche to focus on industrial nonwoven textile waste. Recently human hygene and environmental protection has become another major requirement, resulting in more environmentally benign, natural materials to be used in such applications. Within this context, an industiral waste, developed during the processing of tea leaves was investigated for its sound absorption properties as opposed to a standard woven textile cloth and polyetilen and polyester based nonwoven fibers composed from textile waste. Three different layers of tea-leaf-fiber waste materials with and without backing of a single layer of woven textile cloth were tested for their sound absorption properties. The results indicate that a 1cm thick tea-leaf-fiber waste material with backing, provides sound absorption properties almost equivalent to that of six layers of woven textile cloth. Backed tea-leaf-fibers and nonwoven fiber materials of both with 20mm thickness, exhibit almost equivalent sound absorption properties for the frequency range of 0-3200Hz.
Keywords: Fiber; Insulation; Natural; Sound; Sound absorption; Waste